Comparative occurrence of ESBL/AmpC beta‐lactamase‐producing Escherichia coli and Salmonella in contract farm and backyard broilers. (1st January 2022) - Chowdhury, M.; Bardhan, R.; Pal, S.; Banerjee, Aparna; Batabyal, K.; Joardar, S.N.; Mandal, G.P.; Bandyopadhyay, S.; Dutta, T.K.; Sar, T.K.; Samanta, I.
Abstract: The present study was conducted to detect the occurrence of beta‐lactamase and biofilm‐producing Escherchia coli and Salmonella in apparently healthy broiler birds reared in household and contract poultry farms. In total, 150 cloacal swabs were collected from apparently healthy broiler birds of various age groups reared in backyard ( n = 100) and contract farms ( n = 50) in West Bengal (India). The isolation rate of ESBL producers was significantly more ( P < 0·05) reared in contract poultry farms than those reared in backyard. Majority of the E. coli isolates possessed bla CTX‐M followed by bla SHV and bla TEM . Majority of the Salmonella strains possessed bla TEM followed by bla CTX‐M, and no bla SHV was detected. The selected sequences of the PCR products were found cognate with bla CTX‐M‐1, bla CTX‐M‐2, bla CTX‐M‐9, bla CTX‐M‐14, bla CTX‐M‐15, bla SHV‐12 and bla TEM‐52 . The study detected 46·8% of E. coli and 42·5% of Salmonella strains as biofilm producers. Beta‐lactamase‐producing Enterobacteriaceae strains showed resistance against tetracycline, chloramphenicol, doxycycline, co‐trimoxazole and ampicillin and sensitivity to imipenem‐EDTA, colistin and gentamicin. The study revealed the partial clonal relationship of ESBL sequences possessed by the poultry isolates of the present study and local clinical isolates available in the database. The study made consumer awareness about careful handling of live birds or poultry meat to avoid the zoonotic transmission of antimicrobial‐resistant Enterobacteriaceae.